Enzymatic synthesis of biobased polyesters utilizing aromatic diols as the rigid component. (5th May 2020) - Pellis, Alessandro; Weinberger, Simone; Gigli, Matteo; Guebitz, Georg M.; Farmer, Thomas J.
Graphical abstract: Highlights: Biocatalyzed synthesis of furan and pyridine diols-based polyesters. Tunable crystallinity based on the aliphatic diester used for their synthesis. Complete characterization and analysis of the obtained materials. Abstract: In the present work, the biocatalyzed synthesis of a series of aromatic-aliphatic polyesters based on the aliphatic diesters dimethyl succinate, dimethyl adipate and dimethyl sebacate and the aromatic diols 2, 5-bis(hydroxymethyl)furan, 3, 4-bis(hydroxymethyl)furan and 2, 6-pyridinedimethanol were investigated. A similar series of polyesters based on the petroleum-based 1, 3-benzenedimethanol, 1, 4-benzenedimethanol and 1, 4-benzenediethanol were also synthesized for comparison. Data show that the enzymatic syntheses were successful starting from all diols, with the obtained polymers having isolated yields between 67 and over 90%, number average molecular weights between 3000 Da and 5000 Da and degree of polymerization (DP) of 6–18 (based on the used aliphatic diesters and aromatic diols) when polymerized in diphenyl ether as solvent. Only using 3, 4-bis(hydroxymethyl)furan as the diol led to shorter oligomers with isolated yields around 50% and DPs of 3–5. DSC and TGA thermal analyses show clear correlation between polymer crystallinity and aliphatic carbon chain length of the diester.